PENGARUH INFLASI, KURS, RETURN ON ASSETS DAN RETURN ON EQUITY TERHADAP HARGA SAHAM SEKTOR PERTAMBANGAN DI INDONESIA - Nugraha, Ayu Kinkin Pandu; Riyanto, Wahyu Hidayat; Hadi, Syamsul (Journal of Financial Economics & Investment, 2022)
This study aims to determine the effects of inflation, kurs rupiah, ROA and ROE on stock prices in the mining sector. The data used in this study are secondary data for the period 2016-2020. The dependent variable is the mining stock price, while the independent variables include inflation, kurs rupiah, ROA, and ROE. The Slovin formula was used in the sampling technique. The research method used is panel data regression with the Random Effect Model (REM) as the best chosen model. The results showed that the variables inflation, kurs rupiah, ROA and ROE at the same time, or at least one of them, had a significant impact on share prices in the mining sector. The results of the partial study of the kurs rupiah and the ROE have a positive and significant effect on the share price of the mining sector, while the variables inflation and ROA have a negative and insignificant influence on the share price of the mining sector.